In situ Synchrotron IR Microspectroscopy of CO2 Adsorption on Single Crystals of the Functionalized MOF Sc2(BDC‐NH2)31. (7th November 2014) - Greenaway, Alex; Gonzalez‐Santiago, Berenice; Donaldson, Paul M.; Frogley, Mark D.; Cinque, Gianfelice; Sotelo, Jorge; Moggach, Stephen; Shiko, Elenica; Brandani, Stefano; Howe, Russell F.; Wright, Paul A.
Abstract Synchrotron radiation (SR) IR microspectroscopy has enabled determination of the thermodynamics, kinetics, and molecular orientation of CO2 adsorbed in single microcrystals of a functionalized metal–organic framework (MOF) under conditions relevant to carbon capture from flue gases. Single crystals of the small‐pore MOF, Sc2(BDC‐NH2)3, (BDC‐NH2=2‐amino‐1, 4‐benzenedicarboxylate), with well‐defined crystal form have been investigated during CO2 uptake at partial pressures of 0.025‐0.2 bar at 298–373 K. The enthalpy and diffusivity of adsorption determined from individual single crystals are consistent with values obtained from measurements on bulk samples. The brilliant SR IR source permits rapid collection of polarized spectra. Strong variations in absorbance of the symmetric stretch of the NH2 groups of the MOF and the asymmetric stretch of the adsorbed CO2 at different orientations of the crystals relative to the polarized IR light show that CO2 molecules align along channels in the MOF.